2008
DOI: 10.1158/0008-5472.can-07-5533
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of gadd45a Sensitizes Epithelial Cancer Cells to Ionizing Radiation In vivo Resulting in Prolonged Survival

Abstract: Ionizing radiation (IR) therapy is one of the most commonly used treatments for cancer patients. The responses of tumor cells to IR are often tissue specific and depend on pathway aberrations present in the tumor. Identifying molecules and mechanisms that sensitize tumor cells to IR provides new potential therapeutic strategies for cancer treatment. In this study, we used two genetically engineered mouse carcinoma models, brain choroid plexus carcinoma (CPC) and prostate, to test the effect of inactivating gad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The inactivation of GADD45A causes a disturbance in nucleotide excision repair and proliferation of cancer cells. ( 21 ) GADD45A had a much lower expression in the co‐injection group than in the DU145 alone group, consistent with its tumor suppressive properties. RhoV is a small GTPase with a similar structure and function to another Rho family member, RhoU.…”
Section: Discussionsupporting
confidence: 55%
“…The inactivation of GADD45A causes a disturbance in nucleotide excision repair and proliferation of cancer cells. ( 21 ) GADD45A had a much lower expression in the co‐injection group than in the DU145 alone group, consistent with its tumor suppressive properties. RhoV is a small GTPase with a similar structure and function to another Rho family member, RhoU.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, Zhang et al found that high level expression of Gadd45a sensitized M1 myeloblastic leukemia and H1299 lung carcinoma cell lines to apoptosis induced by gamma-irradiation [28] . However, inactivation of Gadd45a gene has been reported to sensitize transgenic tumor mouse to radiation treatment [29] . In the current study, we further reveal the role of Gadd45a in the response of oral cancer cells to IR treatment using si-RNA.…”
Section: Discussionmentioning
confidence: 99%
“…[143][144][145] While p53 loss (either by mutation abolishing p53 binding to DNA or at the gene level ablating p53 protein expression) correlated with dramatically increased resistance to IR, ablated p21 expression did not correlate with IR sensitivity. 144 This result was controversial as the loss of p21 has been shown to dramatically sensitize a range of cell lines to many other types of DNA damage 119,146,147 suggesting that the default cellular response to DNA damage is to induce apoptosis and that cells express p21 to mediate cell cycle arrest and inhibit apoptosis. Recently there has been significant interest regarding how different p53-responsive genes are turned on or off under different types of cellular stress specifically the regulation of p21 expression.…”
Section: Summary and Future Directionsmentioning
confidence: 99%